Tandem peptide lipid CRISPR-Cas9 complex combating APP and APOE4 gene abnormality in Alzheimer's disease - Ilham Rahmanto; Maulana Bagus Adi Cahyono; Husnul Khatimah; Rahmi Nugraningrum; Pionera Seconda Giyanti Putri; Nurul Zulfa Sahiruddin; Nabila Rahmaniah; Pradana Zaky Romadhon (Universitas Muhammadiyah Surabaya, 2024)
Alzheimer's attacks 24 million global population and dominates 60-80% of existing cases of dementia. It causes the accumulation of beta-amyloid (Aβ) plaques in the hippocampus and entorhinal cortex, resulting in decreased mass from the brain. Recent studies have shown that the manifestation of this disease is due to an overaccumulation of abnormal Aβ protein due to abnormalities in the APP and APOE4 genes. Point mutations in the APP gene will create the toxic form of Aβ protein, namely Aβ42, and the toxic APOE4 gene will accelerate the onset of Aβ42 deposition and pro-inflammatory activity that exacerbates the degenerative process of the brain. Gene editing as a potential definitive therapy was recently a concern by researchers. CRISPR-Cas9 repairs the APP gene and substitutes the APOE4 gene with APOE3 by modifying the gene's DNA sequence. Nano complex CRISPR-Cas9 tandem peptide lipid is a model for clinicians to target brain nerve cells. In vivo research on an Alzheimer's mouse model proved the potential of nano-complex-based peptides as carriers of CRISPR-Cas9 in brain nerve cells. This engineering technology offers satisfactory results with high precision, minimal side effects, and a relatively low price for long-term therapeutic effects and even a lifetime.